Management of peripheral arterial disease in the context of a multidisciplinary limb program - Neville, Richard F. (Frontiers in Cardiovascular Medicine, 2024)
Peripheral artery disease (PAD) continues to increase in prevalence worldwide due to risk factors such as advanced age, diabetes mellitus, and obesity. Critical limb ischemia (CLTI) is the advanced form of PAD that can result in a lack of healing and limb loss as the most devastating consequence. Patients with PAD, especially CLTI, benefit from multidisciplinary care to optimize outcomes by reducing cardiovascular morbidity and mortality and preventing lower extremity amputation. Collaboration between various specialties allows a focus on problems involved in treating the patient with PAD including prevention, screening, medical care, wound care, infection, and revascularization when needed. Although there is no clear definition or consensus on the structure of the PAD team, certain guidelines are applicable to most clinical scenarios emphasizing “provider champions” in leading a clinical program. A vascular specialist (vascular surgery, interventional radiology, interventional cardiology) and a soft tissue specialist (podiatry, plastic surgery) are the typical “champions,” often involving orthopedics, general surgery, vascular medicine, diabetology/endocrinology, infectious disease, nephrology, and rehabilitation medicine. The team should also include wound nurses, nutritionists, occupational therapists, orthotists, pharmacists, physical therapists, prosthetists, and social workers. This paper presents a brief overview of the structure of the multidisciplinary team with key components and functions of such a team to optimize treatment outcomes for PAD and CLTI.